Evaluating the social curriculum for the first intermediate grade from the teachers' point of view - Al Hammadi, Jinan Abdul Karim (Al-Adab Journal, 2021)
There is no doubt that the educational process in general, especially educational curricula, is subject to evaluation processes all over the world, And it starts from the goals, curricula and planning of the educational process, That evaluation represents the fourth element, and it is one of the factors that directly affect the educational process, The evaluation of the educational curriculum is a process whose focus finds importance due to the fundamental role that the curriculum plays in assessing the identity of school education and achieving its goals.